Perkembangan Kelembagaan Dari Negeri Dan Marga Menjadi Desa Di Kecamatan Tungkal Ulu Kabupaten Tanjab Barat Provinsi Jambi - Erdianto ' (Fakultas Hukum Universitas Riau, 2010)
Reveals the historical development of the village or clannamed country means also discuss the history of thelaw on setting up an autonomous region in the small-est administrative structure Indonesia. This paper con-cluded a few things about the growth and develop-ment of villages in the District of West Tanjab TungkalUlu Jambi Province. Adjustment system according tothe form of the village who live in actual Java stuntcapability for autonomous villages.